2021
DOI: 10.2186/jpr.jpor_2019_420
|View full text |Cite
|
Sign up to set email alerts
|

Niobium silicate as a filler for an experimental photopolymerizable luting agent

Abstract: Purpose: To synthesize niobium silicate particles (SiNb) and incorporate into resin-based luting agents. Methods: SiNb particles were synthesized and characterized by x-ray diffraction, FTIR spectroscopy, particle size, and specific surface area. Luting agents were formulated with 50 wt% BisGMA, 30 wt% TEGDMA and 20 wt% UDMA. BAPO was used as a photoinitiator in 1mol%. The SiNb particles were incorporated into the agents at concentrations of 50 wt% (SiNb50%) or 65% wt% (SiNb65%). Barium glass particles at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Regarding the inorganic composition, commercially available resin-matrix cements contain an inorganic content ranging from 57 up to 78 wt% [ 13 , 14 , 19 , 55 , 56 , 57 , 58 , 59 , 60 ]. As shown in Table 1 , colloidal silica, ytterbium, or barium glass are the most frequent inorganic particles used as fillers [ 19 , 61 ]. However, other combinations of fillers have also been used, such as fluoroaluminoborosilicate glass, strontium calcium aluminosilicate glass, quartz, or other glass fillers [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the inorganic composition, commercially available resin-matrix cements contain an inorganic content ranging from 57 up to 78 wt% [ 13 , 14 , 19 , 55 , 56 , 57 , 58 , 59 , 60 ]. As shown in Table 1 , colloidal silica, ytterbium, or barium glass are the most frequent inorganic particles used as fillers [ 19 , 61 ]. However, other combinations of fillers have also been used, such as fluoroaluminoborosilicate glass, strontium calcium aluminosilicate glass, quartz, or other glass fillers [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, other combinations of fillers have also been used, such as fluoroaluminoborosilicate glass, strontium calcium aluminosilicate glass, quartz, or other glass fillers [ 13 ]. The inorganic filler content is responsible for enhanced mechanical properties, although resin-matrix cements usually have a lower filler content when compared with resin-matrix composites [ 58 , 61 ]. Resin-matrix cements reveal a high variability in shape, size, and content of inorganic filler particles [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The increased particle concentration may impair light transmission, reducing the light available through the material 29 . As an amorphous structure is observed for the SiNb particles, the light scattering could likely be limited when compared to other bioactive inorganic particles used as filler for remineralization 17 . Most of the used bioactive particles are based on crystalline oxides 15,18,21,30 with high refractive index (RI 2–3) values that differ from the values obtained in methacrylate 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the used bioactive particles are based on crystalline oxides 15,18,21,30 with high refractive index (RI 2–3) values that differ from the values obtained in methacrylate 31,32 . Previous reports have shown that the SiNb particles presented RI values close to 1.5, similar to the base resin 17,18,28 . Inadequate polymerization is directly related to reduced performance with impaired resistance to degradation and mechanical properties, as well as potential cytotoxic effect 33,34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation